العولمـــة والهويـــــــــة دراسة تطبيقية بشـــــأن الخصوصية الحضاريــة لمجتمـع أقليم كوردستان وتفعيل دورها من خلال الاعلام السياحي - الزهاوى, محمد ابراهيم (Sulaimani Journal for Humanities, 2008)
The study comes of different suggestion and ideas to discuses and analysis it appearance of the result of studies and evaluation of experts in different international communeties in regard of the operation of production and progress especially in R&D and expertise in R&D aiming to put it indiscussion to inrich it and to dispense which is not effective with the target of changing the actual situation in Kurdistan to have a better level agreed by different ideas and different background and dealogies. many of the ideas and the solutions presented for developing of the R&D and the wark of universities and academic center in the region which is made it nesseceray to have in our consideration the up grading of the conscious level (idealogical conisous) by those who are warking in the scientific centers and there acceptance of its necessity for the region. Working on this bases it's necessary to concentrate of the general streams with the aime of stoping the weakness and rancidity in regarded of R&D at the right place which must be on the first stage of national priorities in the region. In this paper we want to discover the clearence of scientific effect which comes from the limitation of spends in regard of association planning program regarding higher education which include in most of R&D programs for different scientific divisions of the universities, collages and technical institution, this prosses as such needs to suitable solutions to ensure bests of benefits the different economic social sectors in the region.